2023
DOI: 10.1088/1755-1315/1208/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Hg-N on ex-gold mining soil ameliorated with Sub-Bituminous coal and activation of Sub-Bituminous coal–NaOH

Abstract: Mercury (Hg) contamination has become a serious threat to ecosystems. Amelioration technology for soil is expected to control the specific interactions between N in ex-gold mining soil contaminated with Hg. This research aimed to analyze the interaction of Hg-N on ex-gold mining soil ameliorated with sub-bituminous coal and the activation of sub-bituminous coal with 10% NaOH. The experimental design used in this study was a Completely Randomized Design with three replications. The treatment I (Sub-bituminous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Various studies have shown the optimal potential of sub-bituminous coal (SC) as an ameliorant soil, starting from its high humic substance (HS) content to its powder form and activation process, which can increase pH, CEC, and soil organic matter (SOM) on marginal lands (Herviyanti et al, 2021;Prasetyo et al, 2023;Maulana et al, 2023). Increased soil pH and CEC are important indicators in studying the phenomenon of modification of negative charge activity in soil (Hermawan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the optimal potential of sub-bituminous coal (SC) as an ameliorant soil, starting from its high humic substance (HS) content to its powder form and activation process, which can increase pH, CEC, and soil organic matter (SOM) on marginal lands (Herviyanti et al, 2021;Prasetyo et al, 2023;Maulana et al, 2023). Increased soil pH and CEC are important indicators in studying the phenomenon of modification of negative charge activity in soil (Hermawan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%